2007
DOI: 10.1111/j.1365-2125.2007.03013.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of plethysmography and oscillometry to compare long‐acting bronchodilators in patients with COPD

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Forced expiratory voume in 1 s (FEV1) is the standard measurement used to measure drug effects in chronic obstructive pulmonary disease (COPD) clinical trials.• Having previously shown that specific airway conductance (sGaw) measured using body plethysmography and impulse oscillometry (IOS) are more sensitive than FEV1 for assessing short-acting bronchodilator effects in patients with COPD, we conducted the first randomized, placebo-controlled study to compare long-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 19 publications
2
56
0
Order By: Relevance
“…Noninvasive measurements of tidal lung mechanics using the forced oscillation method are an attractive alternative to more usual effort dependent tests of pulmonary function and others have shown that such tests are a sensitive way of detecting bronchodilator effects in these patients [41]. However, the change in the total Zrs after a bronchodilator may underestimate the true effects of therapy if expiratory impedance data are not excluded from the analysis in flow-limited patients.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive measurements of tidal lung mechanics using the forced oscillation method are an attractive alternative to more usual effort dependent tests of pulmonary function and others have shown that such tests are a sensitive way of detecting bronchodilator effects in these patients [41]. However, the change in the total Zrs after a bronchodilator may underestimate the true effects of therapy if expiratory impedance data are not excluded from the analysis in flow-limited patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous data, 18 a treatment decrease of 15% in sGaw on the individual treatments compared with the combination was defined as clinically relevant. To detect a decrease of 15% in AUC (0-4 h) sGaw between one of the individual treatments and SFC+TIO with 90% power, a two sided 0.025 significance level and a within subject SD of 0.1652 (log transformed sGaw), it was estimated that 30 subjects would be required to complete at least two active treatment periods.…”
Section: Methodsmentioning
confidence: 99%
“…We used the sensitive pulmonary function measurement of specific airway conductance as the primary end point to compare the different treatment regimens. [18][19][20][21] Pulmonary function measurements of spirometry and lung volumes were also performed, and symptom scores were evaluated.…”
mentioning
confidence: 99%
“…Finally, it was recently shown that ''distal'' oscillometry parameters (R5Hz-R20Hz and X5Hz), measured at baseline breathing and at an elevated respiratory rate (40 breaths?min -1 ), correlated perfectly with the fall of dynamic compliance at 60 breaths?min -1 , a reference invasive technique used to assess the distal airways [124]. Impulse oscillometry is also useful for evaluating responses to short-and long-acting bronchodilators and here it is suggested to be more sensitive than spirometry in comparing drugs [125,126]. The clinical relevance of oscillometry parameters in COPD was recently analysed by HARUNA et al [127].…”
Section: Forced Oscillations and Impulse Oscillometrymentioning
confidence: 99%